Estudos e práticas colaborativas não-presenciais em educação ambiental : implantação de uma solução na Web para interação com as escolas da região de inundação do alto rio Paraná. - Periotto, Tania Regina Corredato (2008)
The project "The Floodplain of the Upper River Paraná" comprises both the activities of three research groups of the State University of Maringá and environmental monitoring coupled to articulations with local communities, among other activities, for possible solutions of environmental issues. The program for the Continuous Study on Environmental Education (PECEA) was planned according to the above-mentioned activities. An interdisciplinary work and the use of Information and Communication Technologies (ICTs) have been established supplemented with practical work on Environmental Education executed with teachers of the Municipal School of Porto Rico PR Brazil. During one year of interactivities results showed digital inclusion of participants and the understanding of several dimensions in Environmental Education from the social and environmental points of view. Results also triggered an interactive type of platform and non-presencial collaboration, or rather, a WEB thematic portal for social and environmental studies. The aims of current text are (1) the description of the construction, structuring and functioning process of the thematic portal and (2) the qualitative evaluation of results according to users' demands. This is done through gradual dissemination and inter-relationships between society and nature which may be alternated by practices that foreground improvement in life quality and in citizenship. The methodological option for the development of the portal was based on (1) structuring and establishment, conducted by the researcher and (2) on activities, characterized as research-activity according to the theme, to make possible the simultaneous engagement of the researcher and the participants, each according to their own roles, albeit with common aims.